An Interactive Learning Environment System on Basic Programming Subjects: Effects of Learning Outcomes and Question Level Patterns - Aulia Akhrian Syahidi; Ahmad Afif Supianto; Herman Tolle; Tsukasa Hirashima (Universitas Negeri Padang, 2022)
This study reports on the effect of using interactive learning environment system by embedding problem-posing and problem-solving learning pattern as a flow of interaction. This interactive learning environment system is attempted as a solution to help understand and learn basic programming in Vocational High Schools. The effects that will be known are student learning outcomes and tracking of question-level patterns. The research method used was a quasi-experimental design with a nonequivalent control group design, involving 36 vocational high school students who were divided into an experimental group (N=18) and a control group (N=18). For data analysis, the technique of independent sample t-test and paired sample t-test was used. The results showed that student learning outcomes on each test there were significant differences after using interactive learning environment system and there was a good improvement in the experimental group compared to the control group. A total of 20 questions are provided for each test with a different pattern. Analysis of the level pattern of questions is done by distinguishing between the database answer key system and student answers. The tracking results showed that on the 1st test the level of accuracy occurred in 12 questions with the easy category and for the 2nd test the accuracy level occurred in 14 questions with the easy category.